2013
DOI: 10.7726/ajad.2013.1002
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Variables that Predict Progression from MCI to AD Dementia over Duration of Follow-up

Abstract: The purpose of this paper is to investigate the relative utility of using neuroimaging, genetic, cerebrospinal fluid (CSF), and cognitive measures to predict progression from mild cognitive impairment (MCI) to Alzheimer’s disease (AD) dementia over a follow-up period. The studied subjects were 139 persons with MCI enrolled in the Alzheimer’s Disease Neuroimaging Initiative. Predictors of progression to AD included brain volume, ventricular volume, hippocampal volume, APOE ε4 two alleles, Aβ42, p-tau181, p-tau1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…This may explain why volumetric changes on MRI were reported to be better predictors than cognitive measures among cognitively normal individuals [32]. A similar point was also made in the literature [33,34]. Our analyses controlled for the presence of APOE and demographic variables that have been associated with cognitive decline or the likelihood of developing AD.…”
Section: Discussionmentioning
confidence: 62%
“…This may explain why volumetric changes on MRI were reported to be better predictors than cognitive measures among cognitively normal individuals [32]. A similar point was also made in the literature [33,34]. Our analyses controlled for the presence of APOE and demographic variables that have been associated with cognitive decline or the likelihood of developing AD.…”
Section: Discussionmentioning
confidence: 62%
“…Most of the current analysis was based on volumes of brain regions 2426 . For example, AD patients and MCI patients have been shown to have 27% and 11% smaller hippocampal volumes, respectively, as compared with normal age-matched elderly 24 .…”
Section: A Motivating Clinical Studymentioning
confidence: 99%
“…In [73], 148 MCI subjects were used to identify the most predictive neuropsychological measures. In [44], 139 MCI subjects in ADNI-1 were used to evaluate the predictive power of brain volume, ventricular volume, hippocampus volume, APOE status, cerebrospinal fluid (CSF) biomarkers, and behavioral scores. Their results show a moderately accurate prediction with the value of an area under the curve of 0.757 at 36 months, whereas they found that baseline volumetric MRI and behavioral scores were selectively predictive.…”
Section: Introductionmentioning
confidence: 99%